Sources of Income Persistence: Evidence from Rural El Salvador - Sosa-Escudero, Walter; Marchionni, Mariana; Arias, Omar (Journal of Income Distribution®, 2011)
This article uses a unique panel data set of rural El Salvador to investigate the main sources of persistence and variability in incomes. Our econometric framework validly reduces a general panel model to a dynamic linear model with a covariance structure that can be estimated efficiently with short panels. We find that life-cycle incomes are largely explained by the productive characteristics of families, such as education and access to public goods, and unobserved heterogeneity. Pure state dependence, arising from income shocks persistency, is of second order. In El Salvador, frequent transitory shocks are a more important source of income variation than in developed countries.